Improving Traditional Health Services Through Kinesiotherapy in an Effort to Reduce the Number of Musculoskeletal Patient Referrals at the Binanaga Mamuju Community Health Center in West Sulawesi - Erna Kena; Vip Paramarta; Rulia; Ayu Laili Rahmiyati; Farida Yuliaty (Green Publisher Indonesia, 2026)
This study aims to analyze the effectiveness of kinesiotherapy as an innovation in traditional health services at the Binanaga Community Health Center, Mamuju, West Sulawesi, as well as its role in reducing the number of referrals for patients with musculoskeletal disorders and increasing patient satisfaction. This study uses a qualitative approach with in-depth interviews and participatory observation involving traditional health workers and patients receiving kinesiotherapyservices. The results show that the implementation of kinesiotherapy is effective and in accordance with applicable operational standards. Kinesiotherapy has a significant impact in reducing pain in patients, increasing satisfaction with services, and contributing to a decrease in the number of referrals to advanced health care facilities. This service also presents challenges, such as limited facilities, restricted service space, and the need for further training for health workers to maintain service quality. The research findings confirm that kinesiotherapy, as part of traditional health services, can serve as an effective initial treatment alternative at the primary care level, with clear clinical benefits and patient satisfaction. In addition, the sustainability of this service requires institutional support, improved infrastructure, and strengthened regulations. This study provides an empirical basis for the development of kinesiotherapy services and their integration into the public health system.